The Meaning of Sasak Women’s Self-Value in Pisuke Culture - Ariyanti, Meilisa Indah; Jumaidi, Lalu Takdir (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to interpret the self-value of Sasak women in Pisuke culture and then reveal the uniqueness of accounting born from this culture. This research uses an interpretive paradigm and ethnography as the research methodology. Data collection techniques were conducted through interviews. Data analysis went through the stages of domain analysis, taxonomy analysis, componential analysis, and uncovering cultural themes. The results revealed that the meaning of Sasak women's self-value in Pisuke culture symbolizes pride, devotion, helping, and appreciation. The nominalization of Pisuke is not in line with the culture of capitalism because Sasak society prioritizes moral and spiritual values. In accounting books, Sasak women's self-value is recognized as assets, liabilities, income, and expenses. Transparency and accountability in Pisuke's culture are needed to maintain trust in Pisuke. The value position contained in Pisuke culture is the value of honesty, the value of sincerity, and the value of justice.